Femoral Head Pathology in Subcapital Hip Fractures: Clinical Value and Cost-Effectiveness in a 230-Patient Case Series - Nissim Ohana; Omer Marom; David Segal; Refael Behrbalk; Yuval Ben-Sira; Alex Tavdi; Ezequiel Palmanovich; Eyal Yaacobi (Diagnostics)
Background/Objectives: Osteoporotic fractures, particularly subcapital hip fractures (SCF), pose a significant healthcare and economic burden. The routine pathological examination of resected femoral heads in such cases is common practice, aimed at identifying malignancies that may have contributed to bone fragility. This study evaluated the cost-effectiveness and clinical utility of routine femoral head pathology in patients undergoing surgical treatment for SCF. Methods: A retrospective cohort study was conducted at a university-affiliated, tertiary care hospital. Patients undergoing surgical treatment for SCF between 2015 and 2018, with available femoral head pathology reports, were included. Data on demographics, prior or active malignancies, surgical procedures, and pathology results were analyzed. Results: The study included 230 patients with a mean age of 82.4 ± 14.1 years, of whom 57% were female. A total of 72 (31%) patients had a history of malignancy at the time of surgery. Pathological examination identified malignancies in eight patients (3.4%), all of whom had active malignancies at the time of admission. The most common malignancies detected were breast cancer and multiple myeloma (three cases each). None of the findings led to changes in patient management. Conclusions: The routine pathological examination of femoral heads following SCF provided a limited diagnostic yield and did not alter clinical management in this cohort. These findings suggest that routine pathology may not be cost-effective and support the adoption of selective screening approaches based on clinical risk factors such as a history of malignancy or atypical fracture presentations.